Analisis Kadar Vitamin C dalam Cabai Rawit (Capsicum frutescens L.) Menggunakan Metode Titrasi Iodometri - Sohabiah, Sohabiah; Muhammad Rizqi (Lembaga Pengembangan Kinerja Dosen, 2025)
Chili pepper (Capsicum frutescent L.) is known as one of the high sources of vitamin C, which acts as an important natural antioxidant for human health because the body is unable to produce its own. This study aims to analyse vitamin C levels in chili pepper using the iodometric titration method quantitatively by taking a 5 gram sample of chili pepper and titrating it using 0,1 N iodine solution. The analysis results showed that the vitamin C content obtained was 0,0704% or equivalent to 70,4 mg/100g. This value is higher than some research results. This value is higher than some previous research results on fruits and chillies from other regions. This finding shows that chilli pepper has great potential as a source of vitamin C in supporting the fulfilment of people’s daily nutrition. In addition, the iodometric titration method is proven to be effective and efficient to be used in the analysis of vitamin C in foodstuffs. Therefore, chili pepper consumption can be a simple strategy in improving nutritional and preventing disease related to vitamin C deficiency.